Synthesis of Iron Nanometallic Glasses and Their Application in Cancer Therapy by a Localized Fenton Reaction. (6th January 2016) - Zhang, Chen; Bu, Wenbo; Ni, Dalong; Zhang, Shenjian; Li, Qing; Yao, Zhenwei; Zhang, Jiawen; Yao, Heliang; Wang, Zheng; Shi, Jianlin
Abstract: Metallic glasses and cancer theranostics are emerging fields that do not seem to be related to each other. Herein, we report the facile synthesis of amorphous iron nanoparticles (AFeNPs) and their superior physicochemical properties compared to their crystalline counterpart, iron nanocrystals (FeNCs). The AFeNPs can be used for cancer theranostics by inducing a Fenton reaction in the tumor by taking advantage of the mild acidity and the overproduced H2 O2 in a tumor microenvironment: Ionization of the AFeNPs enables on‐demand ferrous ion release in the tumor, and subsequent H2 O2 disproportionation leads to efficient . OH generation. The endogenous stimuli‐responsive . OH generation in the presence AFeNPs enables a highly specific cancer therapy without the need for external energy input.